IDENTIFICATION OF SINGLE NUCLEOTIDE POLYMORPHISMS ON CATTLE BREEDS IN INDONESIA USING BOVINE 50K - Puji Lestari; Habib Rijzaani; Dani Satyawan; Anneke Anggraeni; Dwinita Wikan Utami; Ida Rosdianti; Muchamad Lutfi; I Made Tasma (Indonesian Journal of Agricultural Science, 2015)
Single nucleotide polymorphisms (SNPs) abundant in bovine genome influence genetic variation in biological mechanism. The study aimed to identify SNPs on Indonesian cattle breeds and analyze their genetic diversity using Bovine 50K SNP chip. Twenty eight "Ongole Grade" (OG) beef cattle and 20 "Holstein Friesian" (HF) dairy cattle were used for the Infinium II assay test. This assay included amplification of genomic DNA, fragmenta-tion, precipitation, resuspension, hybridization, processing bead chip for single-base extension, and imaging at iScan. Data and clusters were analyzed using GenomeStudio software. The Bovine 50K SNP chip containing 54,609 SNPs was observed spanning all chromosomes of bovine genome. Genotyping for the total SNPs was successfull based on Call Rate, GeneCall and GeneTrain scores. Most SNP markers had alleles that shared among the individuals or breeds, or had specific alleles at distinctive frequencies. Minor allele frequency (MAF) spreads equally with intervals of 0-0.5. The breeds of OG and HF tended to be separated in different clusters without considering their genetic history and twin or normal. This result suggests that most individuals are closely related to one another, regardless of the same breed. Some genes identified on chromosomes 3, 4, 5, 7, 13, 17 and 18 were located in the loci/regions that contained SNPs with specific alleles of either HF or OG breed. These SNPs were more powerful for differentiation of beef cattle and dairy cattle than among individuals in the same breed. These SNP variations and genetic relatedness among individuals and breeds serve basic information for cattle breeding in Indonesia.